Hydroxyapatite Growth on Poly(Dimethylsiloxane-Block-ε-Caprolactone)/Tricalcium Phosphate Coatings Obtained by Electrophoretic Deposition - Redondo, Franco Leonardo; Giaroli, María Carolina; Ciolino, Andrés Eduardo; Ninago, Mario Daniel (Frontiers in Materials, 2022)
For the first time, composite coatings based on poly(dimethylsiloxane-block-ε-caprolactone) copolymer and tricalcium phosphate were obtained on stainless steel plates by using electrophoretic deposition technique. The effect of different deposition times on the final characteristics of the resulting coatings was also studied. Block copolymer was obtained through a combination of anionic and ring-opening polymerization, with good homogeneity and chemical composition (Ð < 1.3 and wPCL = 0.39). The composites obtained at different electrophoretic deposition times revealed a linear dependence between the deposited weight and time during essays. When immersing in simulated body fluid, a higher amount of residual solids (~ 20 %) were observed by thermogravimetric analysis after 7 days of immersion. Scanning electron microscopy micrographs revealed a porous microstructure over the metallic substrate and the absence of micro-cracks, and X-ray diffraction patterns exhibited diffraction peaks associated with a hydroxyapatite layer. Finally, energy-dispersive X-ray analysis revealed values of Ca/P ratio between 1.40 and 1.50 in samples, which are closer to the stoichiometric hydroxyapatite values reported in hard tissues. The results obtained in this paper confirms the usefulness of poly(dimethylsiloxane-block-ε-caprolactone) copolymer and cheaper tricalcium phosphate as precursors of compact and homogeneous coatings obtained by electrophoretic deposition, which yield useful substrates for hydroxyapatite growth.